Humanized care: A relationship of familiarity and affectivity (2015)
ABSTRACT: This work sought to understand the meaning of humanized nursing care in the experience of participants, nurses, patients, and their relatives. Methodology. This was an interpretive phenomenological study based on in-depth interviews, which included 16 adult participants and was conducted in Medellín, Colombia, between December 2012 and March 2013. Results. The patient’s situation, the nurses’ communication skills, and the condition of both, as human beings, influence upon the words, gestures and attitudes during the nurse-patient relationship, where the presence, that which is done, and how it is done permit leaving an important impression on patients and their relatives. Conclusion.The interaction between patients and nurses goes through various stages until achieving the necessary empathy, compassion, affection, and familiarity to account for humanized care.